Astounding structures - Marciniak, Kristin (Unbelievable (12 Story Library (Firm)), 2018)
Highlights twelve incredible structures created around the world from the Akashi Kaikyo suspension bridge in Japan to the 2500 year-old Temple of Hephaestus in Athens. Includes a glossary, resources for further information, and color photographs.